2017
DOI: 10.1053/j.gastro.2017.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Computational Discovery of Niclosamide Ethanolamine, a Repurposed Drug Candidate That Reduces Growth of Hepatocellular Carcinoma Cells In Vitro and in Mice by Inhibiting Cell Division Cycle 37 Signaling

Abstract: BACKGROUND & AIMS Drug repositioning offers a shorter approval process than new drug development. We therefore searched large public datasets of drug-induced gene expression signatures to identify agents that might be effective against hepatocellular carcinoma (HCC). METHODS We searched public databases of mRNA expression patterns reported from HCC specimens from patients, HCC cell lines, and cells exposed to various drugs. We identified drugs that might specifically increase expression of genes that are dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 50 publications
2
82
0
Order By: Relevance
“…1A). This approach was originally proposed in the Connectivity Map project (21), and was extended in other studies (24,65), including a recent study from the Chen lab (23) which used sRGES to quantify the reversal potency and demonstrated its positive correlation with drug efficacy. Sample collection, signature creation, sRGES computation, and in silico validation were streamlined in the OCTAD pipeline which was described in the Materials and Methods section.…”
Section: Results: Identification Of Compounds Which Reverse a Brafi Rmentioning
confidence: 99%
“…1A). This approach was originally proposed in the Connectivity Map project (21), and was extended in other studies (24,65), including a recent study from the Chen lab (23) which used sRGES to quantify the reversal potency and demonstrated its positive correlation with drug efficacy. Sample collection, signature creation, sRGES computation, and in silico validation were streamlined in the OCTAD pipeline which was described in the Materials and Methods section.…”
Section: Results: Identification Of Compounds Which Reverse a Brafi Rmentioning
confidence: 99%
“…Niclosamide was reported to target multiple signaling pathways (e.g., NF‐κB, Wnt/β‐catenin, STAT3, and Notch), most of which are closely involved with cancer stem cells; so it holds promise in eradicating cancer stem cells . Moreover, the in vivo antigrowth effect of niclosamide on HCC was recently evaluated by Chen et al They used patient‐derived xenografts which were established by implanting HCC cells from patients into livers of immunocompromised mice and found niclosamide ethanolamine salt, but not niclosamide effectively slowed growth of patient‐derived xenografts. Although niclosamide and its ethanolamine salt showed the similar antiproliferative effects on HCC cells in vitro, but niclosamide ethanolamine salt was more bioavailable and more effective than niclosamide at slowing the growth of HCC in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We and others [10][11][12][13][14][15][16] have utilized a systems-based approach that employs gene expression profiles of disease samples and drug-induced gene expression profiles from cell lines to discover new therapeutic candidates for diseases. The essential idea is to identify drugs that reverse the disease gene expression signature by suppressing the over-expressed disease genes and activating the repressed genes ( Figure 1A).…”
Section: Mainmentioning
confidence: 99%